Trudności nauczycieli szkół ogólnodostępnych w ocenianiu uczniów z lekką niepełnosprawnością intelektualną - Buchnat, Marzena (Studia Edukacyjne, 2018)
Grading children is of great importance in the educational process. It allows children to learn about their abilities thus shaping their self-esteem and also to define themselves in relation to other people, points to resources and areas for work, builds motivation to undertake further activity, which is why it is particularly important for students with mild intellectual disabilities. However, the grading process is very complex and requires teachers’ knowledge and skills in this area. The aim of the research was to determine what dilemmas in grading students with mild intellectual disabilities teachers of mainstream schools have. The results obtained show that the grading this group of students gives teachers many difficulties and it is therefore necessary to make many changes in this area to make evaluation a factor supporting the effectiveness of education of children with mild intellectual disabilities, and thus a factor that optimizes their development.